2016
DOI: 10.1167/tvst.5.1.5
|View full text |Cite
|
Sign up to set email alerts
|

Axial Length/Corneal Radius of Curvature Ratio and Myopia in 3-Year-Old Children

Abstract: PurposeThis study investigated the association of axial length (AL) to corneal radius of curvature (CRC) ratio with spherical equivalent (SE) in a 3-year old Asian cohort.MethodsThree-hundred forty-nine 3-year old Asian children from The Growing Up in Singapore towards Healthy Outcomes (GUSTO) birth cohort study underwent AL and CRC measurements with a noncontact ocular biometer and cycloplegic refraction using an autorefractor. The ratio of AL to CRC (AL/CRC) was calculated for all the participants, and subse… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
42
2

Year Published

2016
2016
2021
2021

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 44 publications
(46 citation statements)
references
References 22 publications
2
42
2
Order By: Relevance
“…AL/CR RATIO AND RELATIONSHIPS AMONG THE SE AND AL, CR, AND AL/CR RATIO: The distributions of the AL/CR ratio have been reported in different populations and age groups 31,[34][35][36][37][38][39][40][41] and the AL/CR ratios for myopia were between 2.9 and 3.1 and less than 2.9 for emmetropia and hyperopia. 26,27,[42][43][44][45][46] Table 4 summarizes the other studies. In the current report, the CR was approximately the same as that in those previous reports, and women had significantly steeper corneal curvature values, 43 whereas the current AL was longer than those reported previously.…”
Section: Discussionmentioning
confidence: 99%
“…AL/CR RATIO AND RELATIONSHIPS AMONG THE SE AND AL, CR, AND AL/CR RATIO: The distributions of the AL/CR ratio have been reported in different populations and age groups 31,[34][35][36][37][38][39][40][41] and the AL/CR ratios for myopia were between 2.9 and 3.1 and less than 2.9 for emmetropia and hyperopia. 26,27,[42][43][44][45][46] Table 4 summarizes the other studies. In the current report, the CR was approximately the same as that in those previous reports, and women had significantly steeper corneal curvature values, 43 whereas the current AL was longer than those reported previously.…”
Section: Discussionmentioning
confidence: 99%
“…Researches have reported that for children, when cycloplegic refraction is difficult to perform, AL/CR may be the second choice in predicting spherical equivalent. 38,39 In this study, all children received noncycloplegic refraction. There may be bias in refraction directly using noncycloplegic spherical refractive error due to accommodation, thus AL/CR was introduced.…”
Section: Discussionmentioning
confidence: 99%
“…Longitudinal studies indicate that changes in corneal curvature during childhood [36][37][38] and early adulthood [39] are minimal and not associated with the magnitude of myopia progression. However, since the correlation between spherical equivalent refraction (SER) and the axial length to corneal radius ratio is typically stronger than that of axial length alone (by 15-20%) [40][41][42][43], corneal curvature does appear to make a modest contribution to the magnitude of myopia. Although corneal thickness does not vary systematically with refractive error [44][45][46][47], a reduction in corneal hysteresis (an estimate of corneal biomechanical strength or viscoelasticity) has been observed with increasing levels of myopia in children [48,49] and adults [50][51][52].…”
Section: Corneamentioning
confidence: 99%